TYPOLOGIES OF RELIGIOUS MODERATION IN INDONESIAN HIGHER EDUCATION INSTITUTIONS (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
Typologies of religious moderation implementation in several State Islamic Higher Education and Public Higher Education are an interesting subject to discuss. The typologies can demonstrate the road model of educational institutions in building nationality and diversity. This study aims to analyze the typologies of religious moderation practiced at PTKI and PTU with a focus on studies at the State Islamic University Padang, State Islamic University Bandung, and Bogor Agricultural University. By employing a qualitative descriptive approach based on empirical phenomena and collecting data using interviews, participant observation, documentation, and literature review; the research finds that the typologies of religious moderation illustrate an integrative model of institutional and cultural interpolation, symbolic-paradigmatic schemes, internalization of Pendidikan Agama Islam (PAI, Islamic Religious Education) subject, mainstreaming schemes of pesantren mahasiswa, and involvement of extra campus organizations. This study implies that there are various practices of religious moderation in higher educational institutions as models for other higher educational institutions.